NKG2D and Its Ligand MULT1 Contribute to Disease Progression in a Mouse Model of Multiple Sclerosis - Legroux, Laurine; Moratalla, Ana Carmena; Laurent, Cyril; Deblois, Gabrielle; Verstraeten, Sandrine L.; Arbour, Nathalie (Frontiers in Immunology, 2019)
NKG2D is an activating receptor expressed on the surface of immune cells including subsets of T lymphocytes. NKG2D binds multiple ligands (NKG2DL) whose expression are differentially triggered in a cell type and stress specific manner. The NKG2D-NKG2DL interaction has been involved in autoimmune disorders but its role in animal models of multiple sclerosis (MS) remains incompletely resolved. Here we show that NKG2D and its ligand MULT1 contribute to the pathobiology of experimental autoimmune encephalomyelitis (EAE). MULT1 protein levels are increased in the central nervous system (CNS) at EAE disease peak; soluble MULT1 is elevated in the cerebrospinal fluid of both active and passive EAE. We establish that such soluble MULT1 enhances effector functions (e.g. IFN production) of activated CD8 T lymphocytes from wild type but not from NKG2D-deficient (Klrk1-/-) mice in vitro. The adoptive transferred of activated T lymphocytes from wild type donors induced a significantly reduced EAE disease in Klrk1-/- compared to wild type (Klrk1+/+) recipients. Characterization of T lymphocytes infiltrating the CNS of recipient mice shows that donor (CD45.1) rather than endogenous (CD45.2) CD4 T cells are the main producers of key cytokines (IFN, GM-CSF). In contrast, infiltrating CD8 T lymphocytes include mainly endogenous (CD45.2) cells exhibiting effector properties (NKG2D, granzyme B and IFN). Our data support the notion that endogenous CD8 T cells contribute to passive EAE pathobiology in a NKG2D-dependent manner. Collectively, our results point to the deleterious role of NKG2D and its MULT1 in the pathobiology of a MS mouse model.